Evaluation of the functional efficiency of educational services and their geographical distribution in the city of Karabilah - Ahmad, Mahmood Okash (Al-Adab Journal, 2022)
Educational services are the most important basic pillars in building a society and its development, as it is a measure of civilizational, technological and cultural development, and from the analysis and knowledge of the reality of educational services in the city of Karbala, the study showed the presence of four educational stages represented in the primary stage, the middle stage and the middle stage, and the lack and absence of kindergarten stage from the city, The study also revealed that there are (28) primary schools with (12,735) students, and they contain 332 educational divisions, and the number of educational cadres reaches 365 educators. The schools of the stage amounted to (6) schools containing (66) divisions, and the educational cadres in them amounted to (78) educators, while the study showed that the secondary stage consisted of (2) schools and the number of students reached (877), with a total of (18) students. Division and (39) educationally, while the number of schools for the preparatory stage reached (5) schools and included (1759) male and female students, and there were (72) educationally and consisted of (68) educational divisions Which means that the total number of schools in the city of Karabilah has reached (41) schools, and the total number of students in the city for all academic levels amounted to (17,881) male and female students, and they constitute (31.7%) of the total population of the city. The study also revealed the actual need for school buildings. Necessary to relieve the pressure arising from the double-shift system, and the actual need in the future until the target year 2030, which amounts to (72) schools for various educational levels, including the kindergarten stage, which amounts to (18) schools.